Hydraulic model test of wave energy conversion - Suroso, Arief (Penerbit UTM, 2005)
This paper reports the experimental study of wave energy conversion system. The Oscillating Water Column (OWC) has been selected as the primary object of the experimental research. More over, the experimental is a serial research for studying the performance of the OWC. Different models of the OWC have been tested in the previous research. The research reported in the paper tried to apply the reflector in the rear bottom of the cylinder to improve the poor efficiency in the previous models test. The experiment is performed by placing the model in the flume tank and slammed by water wave varied at some wave heights and periods. The reflector position can be changed its slope to obtain the best position for the maximum efficiency. The experimental result indicated that efficiency of the OWC with reflector is better than the OWC without reflector. The model with reflector slope of 450 produced better efficiency compared to the remaining slope. The efficiency for model with reflector increases almost double than the efficiency of the model without reflector (previous experiment).